2023
DOI: 10.1007/s00276-023-03187-8
|View full text |Cite
|
Sign up to set email alerts
|

Congenital external carotid-internal carotid artery anastomosis: a report of three cases and literature review

Abstract: PurposeCongenital external carotid-internal carotid artery (EC-ICA) anastomosis is a cervical arterial variation that was initially reported, based on anatomic dissection, from Japan in 2000. The purpose of this report is to show the characteristic radiological ndings of this extremely rare cervical arterial variation. MethodsWe analyzed nine cases, including six previously reported cases and three cases that we recently experienced. Three of the six previously reported cases were from Japan, and the remaining… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…On reviewing the gures of this case, we concluded that a right nonbifurcating CCA might have formed after occlusion of the ICA channel of EC-ICA anastomosis, as the caliber of the carotid artery changed abruptly at the level of the carotid bifurcation. Only nine cases of congenital EC-ICA anastomosis have been reported [11]. However, one of the nine reported cases is similar to our case [2].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…On reviewing the gures of this case, we concluded that a right nonbifurcating CCA might have formed after occlusion of the ICA channel of EC-ICA anastomosis, as the caliber of the carotid artery changed abruptly at the level of the carotid bifurcation. Only nine cases of congenital EC-ICA anastomosis have been reported [11]. However, one of the nine reported cases is similar to our case [2].…”
Section: Discussionsupporting
confidence: 83%
“…The carotid bifurcation and EC-ICA anastomosis form a large arterial ring. The anastomosis is usually located at the level of the C2 vertebral body, and the ICA channel is smaller than the ECA channel [11]. If the ICA channel is not formed or occluded after development, a nonbifurcating cervical carotid artery may be formed.…”
Section: Discussionmentioning
confidence: 99%